2014
DOI: 10.1093/nar/gku909
|View full text |Cite
|
Sign up to set email alerts
|

SHAPE-Seq 2.0: systematic optimization and extension of high-throughput chemical probing of RNA secondary structure with next generation sequencing

Abstract: RNA structure is a primary determinant of its function, and methods that merge chemical probing with next generation sequencing have created breakthroughs in the throughput and scale of RNA structure characterization. However, little work has been done to examine the effects of library preparation and sequencing on the measured chemical probe reactivities that encode RNA structural information. Here, we present the first analysis and optimization of these effects for selective 2′-hydroxyl acylation analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
178
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(182 citation statements)
references
References 36 publications
4
178
0
Order By: Relevance
“…The resulting cDNAs were prepared for sequencing following the in-cell SHAPE-Seq protocol, sequenced on an Illumina MiSeq and analyzed by the standard SHAPE-Seq computational pipeline ( Fig. 1B; Aviran et al 2011a,b;Lucks et al 2011a;Loughrey et al 2014). The output of an in-cell SHAPE-Seq experiment is a reactivity spectrum for a specific RNA that indicates the scaled probability that each nucleotide in the RNA was modified by 1M7 in the cell.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting cDNAs were prepared for sequencing following the in-cell SHAPE-Seq protocol, sequenced on an Illumina MiSeq and analyzed by the standard SHAPE-Seq computational pipeline ( Fig. 1B; Aviran et al 2011a,b;Lucks et al 2011a;Loughrey et al 2014). The output of an in-cell SHAPE-Seq experiment is a reactivity spectrum for a specific RNA that indicates the scaled probability that each nucleotide in the RNA was modified by 1M7 in the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Reactivity spectra were calculated using Spats v0.8.0 and a number of utility scripts to prepare the Illumina output for Spats following previous work (Loughrey et al 2014). Illumina adapter sequences were trimmed from each read using the FASTX toolkit (http ://hannonlab.cshl.edu/fastx_toolkit/) and then aligned to the target RNA sequences with Bowtie 0.12.8 (Langmead et al 2009) based on the input sense and antisense RNAs to determine locations of modifications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used this model to relate reactivity values to corresponding variances by scaling a standard Gaussian noise term for each reactivity. Five noise levels were applied to the data with variances monotonically increased from 1 to 10,000 by factors of 10, starting at values previously observed in experimental data (Loughrey et al 2014). Interestingly, all schemes are robust to noise up to a factor of 100 (Supplemental Fig.…”
Section: Evaluating Scheme Robustness To Noisementioning
confidence: 89%
“…In the absence of biological replicates, we resorted to simulations. Our previous analysis of a different, yet related, probing data set (Loughrey et al 2014) revealed heteroskedasticity, which we modeled to capture this additional complexity (K Choudhary, NP Shih, F Deng, M Ledda, B Li, S Aviran, in prep.). We used this model to relate reactivity values to corresponding variances by scaling a standard Gaussian noise term for each reactivity.…”
Section: Evaluating Scheme Robustness To Noisementioning
confidence: 99%